Performance and Behaviour of Ground Granulated Blast Furnace Slag Imparted to Geopolymer Concrete Structural Elements and Analyzed with ANSYS. (13th October 2016) - Antonyamaladhas, Maria Rajesh; Chachithanantham, Selvamony; Ramaswamy, Anandakumar
Abstract : This paper deals with the behaviour of geopolymer concrete using ground granulated blast furnace slag and steel fibre to compare with M40 grade cement concrete. The cast GPC specimens were placed in a hot curing chamber at 60 ∘ C temperature for 24 hours and tested after 1, 7, 14, and 28 days of ambient curing to find the strength and durability of hardened concrete. The optimum value of compressive strength was attained at 12 Molarities. Fly ash was replaced by GGBS in GPC with different proportions such as 0% to 60% at 5% interval; the optimum strength value was obtained on 40% replacement. From the test results, the compressive, split-tensile, and flexural strength of GPC specimens were 20%, 43%, and 53% higher than those of the control specimens. Based on the optimum strength mix proportion, the structural elements were cast to investigate the stress-strain relations. The GPC beam and L-section showed 33% and 16% higher value. From the results of acid and sulphate resistance tests, it was found that the strength and weight ratio of GPC were higher than the control specimens. From the simulations, it was found that the experimental test results were approximately equal to the ANSYS.